Judicial Enforcement of Constitutional Conventions: Examining the Misleading Idrisur Rahman (Dhaka University Law Journal, 2025)
The provision that the President is required to “consult” with the CJ to appoint the Judges of the SC was a constitutional convention for the most part during the period between 1975- 2011. This convention of “consultation” was enforced by the SC in Bangladesh v Idrisur Rahman in the backdrop of non-confirmation by the Executive of some Judges as permanent Judges of the HCD even after the CJ’s positive recommendation to that effect. To enforce the convention, the Court measured laws of the Constitution in the same parlance as the conventions of the Constitution; that is, it did not find any distinction between laws of the Constitution and established conventions. The Court thus adopted a historical approach to conventions. But, to this author’s view, the Constitution of Bangladesh indicates a positivist approach to conventions. The paper also submits that in deciding the issue of enforcement of conventions, two aspects are particularly significant, which the Idrisur Rahman Court completely omitted in its analysis: first, the effect of the operation of conventions on laws of the Constitution; second, whether conventions are per se law or simply a material and non-binding source of law under the Constitution. Failure to address these issues has both rendered the judgment less convincing and has weakened its authority as a precedent. This paper aims to provide for these omissions of the Court. The attempt may be of guidance for the Court in any future litigation dealing with conventions in general or judicial enforcement of conventions.Dhaka University Law Journal, 2025, 36 (1), 39-63